ROLE EXPRESSION AND POSITION OF BUNDO KANDUANG IN MINANGKABAU NOVELS DURING THE NEW ORDER - Erizal Gani; Zulfikarni Zulfikarni; Yasnur Asri (International Conference on Languages and Arts, 2014)
The research is carried out to describe the role and position of bundo kandung  as woman who was  instrumental in the formation of the next generation character in the local Minangkabau’s novels during the new order. The novels of the research subject are Warisan by Khairul Harun, Bako by Darman Moenir, Orang-Orang Blanti and Negeri Perempuan by Wisran Hadi, and  TamboSebuah Pertemuan by Gus Tf. Sakai. The research uses qualitative description method, and content analysis approach. The result shows that the role and position of women as bundo kandung have been carried out well enough both as a wife and a mother. However, some might just take advantage materially from spouses in which the women or wives cannot stay when things go wrong in their family. The role of women in father’s family is more talked about in Bako, rather than being a woman as a birth mother because Man’s mother, one of the characters in the novel, is mentally ill. Therefore, it is reasonable for bako (sister of father) to take over his mother’s responsibility and build a virtuous personality based on religion and culture in Minangkabau society to nurture him. Even so, the role of women as bundo kandung is shown through bako’s attitude in taking care of their brother’s children. In the novel, Orang-Orang Blanti, bundo kandung is supposed to be taken into account of the Minangkabau tradition. But, their position does not work as it is. The reason for this is men who get the title as penghulu or mamak hold more power than bundo kandung does. Negeri Perempuan also shows that bundo kanduang’s authority is getting lessened in the eyes of Minangkabau community. Bundo is simply a people’s symbol, but not to own full rights in the formation personality children and children in his family. The novel Tambo describes women as bundo kandung have a great responsibility for their family, community, and husband’s community. In this novel visible that women are not only responsible for the formation of children’s personality, but is also able to protect her husband’s family.   Keywords: bundo kandung, novel, Minangkabau tradition, new order.